Outcome of relapse after allogeneic HSCT in children with ALL enrolled in the ALL‐SCT 2003/2007 trial. (28th November 2017) - Kuhlen, Michaela; Willasch, Andre M.; Dalle, Jean‐Hugues; Wachowiak, Jacek; Yaniv, Isaac; Ifversen, Marianne; Sedlacek, Petr; Guengoer, Tayfun; Lang, Peter; Bader, Peter; Sufliarska, Sabina; Balduzzi, Adriana; et al.
Summary: Relapse remains the major cause of treatment failure in children with high‐risk acute lymphoblastic leukaemia (ALL) undergoing allogeneic haematopoietic stem‐cell transplantation (allo‐SCT). Prognosis is considered dismal but data on risk factors and outcome are lacking from prospective studies. We analysed 242 children with recurrence of ALL after first allo‐SCT enrolled in the Berlin‐Frankfurt‐Munster (BFM) ALL‐SCT‐BFM 2003 and ALL‐SCT‐BFM international 2007 studies. Median time from allo‐SCT to relapse was 7·7 months; median follow‐up from relapse after allo‐SCT until last follow‐up was 3·4 years. The 3‐year event‐free survival (EFS) was 15% and overall survival (OS) was 20%. The main cause of death was disease progression or relapse (86·5%). The majority of children (48%) received salvage therapy without second allo‐SCT, 26% of the children underwent a second allo‐SCT and 25% received palliative treatment only. In multivariate analyses, age, site of relapse, time to relapse and type of salvage therapy were identified as significant prognostic factors for OS and EFS, whereas factors associated with first SCT were not statistically significant. Combined approaches incorporating novel immunotherapeutic treatment options and second allo‐SCT hold promise to improve outcome in children with post allo‐SCT relapse.